2009
DOI: 10.1111/j.1532-5415.2009.02274.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Process of Pain Care in Nursing Homes: A Literature Synthesis

Abstract: Regulatory agencies, researchers, and clinicians have identified improving pain assessment and management in nursing homes as a high priority, but there is no consensus regarding the best strategies to change pain management practices in nursing homes. The goal of this article is to present a synthesis of published literature of process-level pain management improvement projects in nursing homes and identify and describe the role and necessary skills of various clinicians and nursing leaders in successful inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…Many recent efforts have focused on improving NH pain care and have emphasized multimodal approaches incorporating better pain assessment methods, better communication between staff and clinicians, pharmacological and nonpharmacological treatments, and training and education. [40][41][42] For example, one initiative in 49 long-term care facilities increased the proportion of residents in pain receiving analgesics from 83% (similar to the current study prevalence) to 90%. 42 In the current study, many residents received a prescription analgesic in the 30-day window before they experienced persistent pain under the definition (subsequent MDS measurement with moderate or severe daily pain).…”
Section: Implications For Research and Practicesupporting
confidence: 70%
See 1 more Smart Citation
“…Many recent efforts have focused on improving NH pain care and have emphasized multimodal approaches incorporating better pain assessment methods, better communication between staff and clinicians, pharmacological and nonpharmacological treatments, and training and education. [40][41][42] For example, one initiative in 49 long-term care facilities increased the proportion of residents in pain receiving analgesics from 83% (similar to the current study prevalence) to 90%. 42 In the current study, many residents received a prescription analgesic in the 30-day window before they experienced persistent pain under the definition (subsequent MDS measurement with moderate or severe daily pain).…”
Section: Implications For Research and Practicesupporting
confidence: 70%
“…Based on these findings, changes in NH pain practices may be needed. Many recent efforts have focused on improving NH pain care and have emphasized multimodal approaches incorporating better pain assessment methods, better communication between staff and clinicians, pharmacological and nonpharmacological treatments, and training and education . For example, one initiative in 49 long‐term care facilities increased the proportion of residents in pain receiving analgesics from 83% (similar to the current study prevalence) to 90% .…”
Section: Discussionsupporting
confidence: 56%
“…Recommendations to improve pain assessment and management in nursing homes, including national guidelines, have stressed the importance of a well-trained, knowledgeable pain team 55,56. In addition, implementation of treatment algorithms and consultation, continuous education, and team building within the care team are seen as the cornerstones of better pain management (Table 2).…”
Section: Organizational and Educational Aspects That Challenge Pain Mmentioning
confidence: 99%
“…In addition, implementation of treatment algorithms and consultation, continuous education, and team building within the care team are seen as the cornerstones of better pain management (Table 2). 56 A Canadian study that consulted frontline staff and administrators in long-term care revealed overall a general attitude that is open to change in which staff acknowledged the need for better implementation of pain management. Stakeholders identified a number of barriers including a lack of resources and lack of support from funding bodies.…”
Section: Organizational and Educational Aspects That Challenge Pain Mmentioning
confidence: 99%
“…Specialty care programming that targets patients at risk for nurse-sensitive clinical issues is one potential measure of care processes because it suggests that clinical nursing expertise is present to address these care issues. We hypothesize, therefore, that greater RN jurisdiction will relate to a nursing home having specialty care programs across a wide range of clinical issues that require nursing expertise (Hypothesis 2), including hospice and palliative care (Stevenson & Bramson, 2009; Suhrie et al, 2009), pain management (Herman, Johnson, Ritchie, & Parmelee, 2009; Swafford, Miller, Tsai, Herr, & Ersek, 2009), dementia care and behavior problems (Luo, Fang, Liao, Elliott, & Zhang, 2010; Nobili et al, 2008), continence care (Leung & Schnelle, 2008; Palmer, 2008; Schnelle et al, 2010), wound care (Frain, 2008; Lynn et al, 2007; Vu, Harris, Duncan, & Sussman, 2007), and restorative care (Resnick et al, 2009). …”
Section: Theoretical Foundation and Research Hypothesesmentioning
confidence: 99%